2020
DOI: 10.1136/jmedgenet-2019-106519
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations in the new E1’ cryptic exon of the VHL gene in patients with tumours of von Hippel-Lindau disease spectrum or with paraganglioma

Abstract: BackgroundsThe incidence of germline mutations in the newly discovered cryptic exon (E1’) of VHL gene in patients with von Hippel-Lindau (VHL) disease and in patients with paraganglioma or pheochromocytoma (PPGL) is not currently known.MethodsWe studied a large international multicentre cohort of 1167 patients with a previous negative genetic testing. Germline DNA from 75 patients with a single tumour of the VHL spectrum (‘Single VHL tumour’ cohort), 70 patients with multiple tumours of the VHL spectrum (‘Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This fact combined with the limited number of studies assessing vHL type 2C participants may have contributed to an overestimation of the frequency of PPGL in this subtype. Another limitation concerns the recently described germline mutations in the E1’ cryptic exon of the VHL gene in patients previously considered mutation negative, consisting of a small subset of patients possibly not assessed in the studies included in this meta-analysis ( 94 ). Another limitation concerns the lack of important information provided by primary studies, namely regarding sociodemographic data of the vHL participants and adequate characterization of PPGL when these occurred (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This fact combined with the limited number of studies assessing vHL type 2C participants may have contributed to an overestimation of the frequency of PPGL in this subtype. Another limitation concerns the recently described germline mutations in the E1’ cryptic exon of the VHL gene in patients previously considered mutation negative, consisting of a small subset of patients possibly not assessed in the studies included in this meta-analysis ( 94 ). Another limitation concerns the lack of important information provided by primary studies, namely regarding sociodemographic data of the vHL participants and adequate characterization of PPGL when these occurred (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This has previously been observed in patients with VHL from two separate studies in which a germline mutation was identified within the intron 1 of the VHL gene that created a cryptic exon. 17 18 This cryptic exon (termed E1’) dysregulated VHL splicing and resulted in loss of protein expression and the germline mutation would not have been detected by standard genetic testing. 17 18 Whereas, an example of the second scenario would be mutation of the TCEB1 gene which is another component of the VHL E3 ligase complex and has been reported as a potential mimic for VHL loss in sporadic ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“… 17 18 This cryptic exon (termed E1’) dysregulated VHL splicing and resulted in loss of protein expression and the germline mutation would not have been detected by standard genetic testing. 17 18 Whereas, an example of the second scenario would be mutation of the TCEB1 gene which is another component of the VHL E3 ligase complex and has been reported as a potential mimic for VHL loss in sporadic ccRCC. 19 20 This report identifies a germline translocation that disrupts the VHL gene as a novel mechanism of gene loss in VHL that would not be detected by standard genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Buffet et al studied the incidence of germline mutations in the cryptic exon (E1′) of VHL gene in patients with VHL disease, and in patients with PCC or PGL. They demonstrated that E′ VHL variants are rare, but nearly as frequent as the VHL variants in exons 1 and 2 in patients with PCC or PGL [ 174 ]. Hergovich et al discovered that VHL—specifically cytosolic VHL30—interacts with microtubules in vivo, and that amino acid residues 95–123 are necessary for microtubule stabilization and binding [ 98 ].…”
Section: Clinical and Genetic Features Of Selected Manifestations Of ...mentioning
confidence: 99%